Hubungan Intensitas Keikutsertaan Pelatihan, Latar Belakang Pendidikan, Pengalaman Kerja Dan Motivasi Kerja Dengan Kinerja Instruktur Lembaga Kursus Dan Pelatihan Di Kabupaten Kulon Progo - Faizatunnisa' Khoiroti, Dian Korprianing Nugraha (Universitas Sarjanawiyata Tamansiswa, 2024)
The purpose of this study is to know the relationship between the intensity of training participation and the performance of instructors, find out the relationship of educational background with instructor performance, know the relationship of work experience with instructor performance, know the relationship of work motivation with instructor performance and know the relationship of training participation intensity, educational background, work experience and work motivation simultaneously with instructor performance. This type of research is quantitative research. Sampling uses the census method as 40 people. Data collection using questionnaires. Data analysis use multiple regression analysis. The result there is a positive and significant relationship between the intensity of training participation and the performance of the instructor, there is a positive and significant relationship between the educational background and the performance of the instructor, there is a positive and significant relationship between work experience and the performance of the instructor, there is a positive and significant relationship between work motivation and the performance of the instructor and there is a positive and significant relationship between the intensity of participation training, educational background, work experience and work motivation simultaneously with the performance of instructors of the Course and Training Institute in Kulon Progo Regency.